ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL PADA PERUSAHAAN REAL ESTATE DAN PROPERTY YANG TERDAFTAR DI BEI - Yesika, Intan; Purba, Mortigor Afrizal (SCIENTIA JOURNAL, 2019)
This study aims to analyze the effect of asset structure, profitability, liquidity on the capital structure. This study uses 165 samples of property and real estate companies listed on the Indonesia Stock Exchange in the period 2012-2016 using purposive sampling method. In this study the capital structure was measured using the Debt to Asset Ratio (DAR) ratio. The method of analysis of this study uses multiple linear regression test using SPSS version 22. The results of this study based on the results of the t test showed the value of the structure of assets t counted -7.575 in the negative direction where t count <t table or -7.575 <1.654 with a significance value of 0,000 which is less than 0.05, which means that the structure of fixed assets has a negative and significant effect on DAR. Profitability has a positive and significant effect on DAR with t count> t table or 2.989> 1.654 with a positive direction with a value of sitgnification of 0.003 <0.05, while liquidity has a negative effect and significance to DAR with t count <t table or -11.128 <1.654 with negative direction with a significance value of 0.000 <0.05. The results of the F test show that the calculated F value> F table is 53,150> 2,660. The meaning of independent variables has a significant influence on DAR. Test of the coefficient of determination (R2) shows the results of Ajustted R Square of 0.490, which means that the DAR variable can be explained by the variables studied by 49%, while 51% is explained by other variables not included in this study. Keywords: Assets Structure, Profitability, Liquidity, Debt to Asset Ratio (DAR)